Implementasi Kebijakan Ketahanan Pangan di Desa Wiwitan Timur - Jasin, Musafir; Amra, Amra; Wahyuti, Sri (Saraq Opat: Jurnal Administrasi Publik, 2026)
Village food security is one of the national development priorities implemented through the Village Fund policy to enhance food availability, accessibility, and utilization at the community level. This study aims to analyze the implementation of village food security policy in Wiwitan Timur Village and to identify factors influencing the effectiveness of its implementation. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Research informants consist of village government officials, BUMDes managers, farmer groups, and beneficiary communities, selected using purposive sampling. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the village food security policy has been implemented through village planning and budgeting mechanisms and realized in various program activities. However, the implementation has not yet been fully optimal. Major constraints include limited policy communication, low human resource capacity, weak coordination among stakeholders, and an implementation orientation that remains largely administrative. These conditions have resulted in the suboptimal contribution of food security programs to enhancing community self-reliance and welfare. This study recommends strengthening the capacity of implementers, increasing community participation, and integrating cross-sectoral programs to achieve sustainable village food security.